Analisis Program Sanitasi Pedesaan dalam Pemanfaatan Jamban di Desa Simpang Lancang Kabupaten bener Meriah - Sri Wahyuni; Eliska Eliska (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Community understanding of clean and healthy living behavior is still lacking, especially in the use of latrines. The research objective was to analyze rural sanitation programs in the use of latrines in Simpang Lancang Village, Bener Meriah Regency. This type of research is descriptive qualitative with a case study design. There were 9 research informants. Data collection techniques with interviews, observation, and visual images. The research results obtained are the community's seriousness in planning the construction of quality, sustainable, and environmentally sound sanitation infrastructure and facilities as well as increasing public awareness of Clean and Healthy Behavior (PHBS). The conclusion of the research is that the rural sanitation program has succeeded in making use of latrines in the village through several important stages of activity starting from the preparation stage, the construction implementation stage, and the post-construction stage. The recommendation of this research is that it is hoped that there will be continuity of programs in the same or other similar forms that are community-based in order to improve public health status